Decreased Risk in the Pancreatic Cancer With History of Hay Fever: A Meta-Analysis - Wang, Guannan; Xu, Zhiwei; Zhu, Jie; Ren, Jiayu; Chen, Mina; He, Guijuan; Yu, Beibei (Frontiers in Public Health, 2020)
Abstract Background An increasing incidence of pancreatic cancer has been observed worldwide over the last few decades. Previous reports suggested that hay fever, a common allergic disease, may function in pancreatic cancer. Data on hay fever as risk or protective factors for pancreatic cancer are controversial probably because most studies have used mixed groups of allergies in a case–control setting. So, we here did a meta-analysis on published studies to evaluate the association of hay fever and the risk of pancreatic cancer. Methods A comprehensive literature searching was performed through the public databases. The association between hay fever and pancreatic cancer was evaluated by odds ratios (ORs) and 95% confidence intervals (CIs). The Cochran’s Q test and I2 index were used to evaluate heterogeneity. Results We included 8 population-based case control studies involving 10454 participants from 1986– 2014. A history of hay fever was associated with a decreased risk of pancreatic cancer (OR, 0.57; 95% CI, 0.50- 0.64, P< 0.00001) through fixed effect model. Case control studies included were all of high quality with no potential publication bias. Conclusion The result of our study suggested that hay fever may significantly decrease the risk of pancreatic cancer.